2020
DOI: 10.3390/toxins12030154
|View full text |Cite
|
Sign up to set email alerts
|

Cyanotoxins Occurrence in Portugal: A New Report on Their Recent Multiplication

Abstract: Historical reports show that in Portugal, cyanotoxins reports were mainly in the Center (cylindrospermopsins) and South (cylindrospermopsins, saxitoxins) regions of the country apart from the well distributed microcystins. Therefore, in our study, seven freshwater ecosystems located in the North and Center Regions of Portugal were screened between April and September of 2017 for the main cyanotoxins (microcystins, cylindrospermopsins, anatoxin-a, and saxitoxins) by a two methods approach that combined the appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Osswald et al [77], although without toxin identification in environmental samples, reported isolated strains from genus Anabaena, Aphanizomenon, Microcystis, and Oscillatoria as ATX-a producers. Moreira et al [28] identified ATX-a (ELISA: Enzyme-Linked Immunosorbent Assay) and the anaC gene in some environmental samples (freshwater).…”
Section: Toxigenic Cyanobacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Osswald et al [77], although without toxin identification in environmental samples, reported isolated strains from genus Anabaena, Aphanizomenon, Microcystis, and Oscillatoria as ATX-a producers. Moreira et al [28] identified ATX-a (ELISA: Enzyme-Linked Immunosorbent Assay) and the anaC gene in some environmental samples (freshwater).…”
Section: Toxigenic Cyanobacteriamentioning
confidence: 99%
“…In Lake Rasa da Serra Devassa, the presence of sxtA in the sample from February 2016 (Table S5) might be due to unknown STX producing strains of Dolichospermum (Table S4). In Portugal's mainland, STX has been reported, similarly to ATX-a, with an identification of a producing strain of Aphanizomenon flos-aquae [86] and identification of SXT through ELISA and identification of biosynthesis genes (sxtG and sxtI) in some environmental samples [28].…”
Section: Toxigenic Cyanobacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, the presence of cyanobacteria in the water bodies of many countries has been extensively studied [ 38 , 43 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. At least eight countries have initiated national programs on water quality and cyanobacterial problems (Australia, Brazil, Canada, Finland, Great Britain, Japan, Portugal and the United States).…”
Section: Introductionmentioning
confidence: 99%
“…The scientific production related to cyanotoxins in countries like Portugal has been enormous in recent years. Moreira et al [ 10 ] presented an update of the current situation by focusing on the recent increase in both toxin events and the number of detected toxic compounds, and the importance of the methodologies followed.…”
mentioning
confidence: 99%